KOMITMEN ORGANISASI DAN MOTIVASI SEBAGAI PEMODERASI HUBUNGAN SISTEM PENGENDALIAN INTERN PEMERINTAH, KOMPETENSI SUMBER DAYA MANUSIA, DENGAN KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Theophilia Fina Leiwakabessy (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2021)
ABSTRACT This study aims to examine organizational commitment and motivation as moderated the relationship between government internal control systems and human resource competence with local government financial statements. The population of this research are government officer in Kabupaten Maluku Barat Daya. Sampling was conducted using a judgment sampling method and number of samples are 44 respondents. The data collection technique used was a survey technique using a questionnaire. Data analysis used moderated regression analysis (MRA). The results showed that the government internal control system do not significantly effect on the quality of local government financial statement, while human resource competence had a significant efect on quality of local government financial statement human resource competence had an effect on the quality of regional government financial reports. Furthermore, organizational commitment can moderate the relationship between government internal control system and the quality of local government financial statement but cannot moderate the relationship between human resource competency and quality of local government financial statement. Meanwhile, motivation can moderate the relationship between human resource competency and the quality of local government financial statement but it fails to moderate the relationship between government internal control system and the quality of local government financial statement’ Keywords: Government Internal Control System, Human Resource Competence, Organizational Commitment, Motivation, Regional Government Financial Statements